2014
DOI: 10.1021/nn4059067
|View full text |Cite
|
Sign up to set email alerts
|

Self-Organization of Amine-Based Cathode Interfacial Materials in Inverted Polymer Solar Cells

Abstract: We present a strategy to fabricate polymer solar cells in inverted geometry by self-organization of alcohol soluble cathode interfacial materials in donor-acceptor bulk heterojunction blends. An amine-based fullerene [6,6]-phenyl-C61-butyric acid 2-((2-(dimethylamino)-ethyl)(methyl)amino)ethyl ester (PCBDAN) is used as an additive in poly(3-hexylthiophene) (P3HT) and 6,6-phenyl C61-butyric acid methyl ester (PCBM) blend to give a power conversion efficiency of 3.7% based on devices ITO/P3HT:PCBM:PCBDAN/MoO3/Ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
79
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(87 citation statements)
references
References 51 publications
8
79
0
Order By: Relevance
“…22,[32][33][34][35] The surface energies of ITO, pDPP5T-2, PCBM, Phen-NaDPO, pDPP5T-2:PCBM and pDPP5T-2:PCBM:Phen-NaDPO were determined by measuring the droplet's contact angle for three liquids (ultrapure water, diiodomethane and ethylene glycol) using the Owens-Wendt and Kaelble method (Fig. 3a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…22,[32][33][34][35] The surface energies of ITO, pDPP5T-2, PCBM, Phen-NaDPO, pDPP5T-2:PCBM and pDPP5T-2:PCBM:Phen-NaDPO were determined by measuring the droplet's contact angle for three liquids (ultrapure water, diiodomethane and ethylene glycol) using the Owens-Wendt and Kaelble method (Fig. 3a).…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al 22 demonstrated that aminobased cathode interfacial materials (fullerene [6,6]-phenyl-C 61 -butyric acid 2-((2-(dimethylamino)-ethyl)(methyl)amino)ethyl ester (PCBDAN) and poly[(9,9-bis(3-(N,N-dimethylamino)propyl)-2,7-uorene)-alt-2,7-(9,9-dioctyluorene)] (PFN)) improve electron selective contacts with ITO when added into the P3HT:PC 61 BM solution at small concentrations. Lee et al 23 showed that polyethyleneimine (PEI) aligned on top of PEDOT:PSS when mixed into the photoactive materials, thereby signicantly simplifying the multi-junction processing.…”
Section: -27mentioning
confidence: 99%
“…By the Knoevenagel condensation of compound DCHO3TIDT with 2-ethylhexyl cyanoacetate or 2-(1,1-dicyanomethylene)-3-octyl rhodanine, the target molecules DCAO3TIDT and DCNR3TIDT were afforded. The exact structures of the two molecules were confirmed by 1 H NMR spectra, 13 C NMR spectra and other methods.…”
Section: Synthesis Of the Moleculesmentioning
confidence: 98%
“…Power conversion efficiency (PCE) which is higher than 9% has been reached recently [2][3][4][5][6][7][8][9][10][11][12][13][14]. Currently, BHJ OSCs are based on two types of donor materials, conjugated polymers and small molecules [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…2,3,6,7 So far, these materials are rarely applied in the active layer of organic electronic devices because of the poor performance. [8][9][10][11][12][13] Therefore, understanding the influence of polar groups on photovoltaic performance of organic semiconductors is important for future materials development. In our previous work, an alcohol soluble narrowband-gap conjugated polymer and an alcohol soluble fullerene derivative, which were both functionalized with tertiary amino group, were synthesized and used as the donor and acceptor material in the active layer of polymer solar cell (PSC).…”
mentioning
confidence: 99%